2020
DOI: 10.5812/aapm.98969
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Preoperative State Anxiety and Pain Six Weeks After Surgical Correction of Pectus Excavatum

Abstract: Background: Pain is a major concern in the early postoperative phase after correction of pectus excavatum. Most studies only focus on pain management in the first days after surgery and describe methods to alleviate the pain immediately postoperatively. The severity of postoperative pain may be influenced by anxiety. So far, few studies have looked into the relationship between anxiety and postoperative pain after pectus excavatum correction. Objectives: This study aimed to investigate the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is known that the level of experienced pain is influenced by several factors, such as depression, stress, anxiety, pain catastrophizing, and insomnia. Patients are informed about the severe postoperative pain that may occur, and this may induce anxiety (14). Studies also suggest pain-related anxiety as one of the most important variables contributing to the development and persistence of pain (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the level of experienced pain is influenced by several factors, such as depression, stress, anxiety, pain catastrophizing, and insomnia. Patients are informed about the severe postoperative pain that may occur, and this may induce anxiety (14). Studies also suggest pain-related anxiety as one of the most important variables contributing to the development and persistence of pain (15).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies have been published which investigate QoL, psychological, social and behavioural outcomes of PEx surgery, the major characteristics of which are shown in online supplemental table 2 49–64. Fourteen of the studies were prospective, uncontrolled cohort studies (before-and-after design) 3 49–51 54–57 59–61 65. A single one of these was multicentre.…”
Section: Resultsmentioning
confidence: 99%
“…Other perioperative factors, such as pain and anxiety, increase inflammatory mediators (COX) that lead to increased PGE2 levels pain and anxiety also increase immunosuppression by decreasing NK cell levels, further hindering the host's ability to recognize and combat tumor cells (44). It has also been shown that, with increased surgical trauma and patient anxiety, there is an increase in β-adrenoceptor signaling, which contributes to increased metastasis and tumor recurrence (47,48).…”
Section: Surgical Stress Responsementioning
confidence: 99%